Analisis Peran Laundry Attendant Dalam Menunjang Kualitas Pelayanan di Housekeeping Departement Gran Puri Hotel Manado - Koapaha, Chrisye Samiun; Mikhael C.S.Mangolo; Jongky W.A. Kamagi (Jurnal Ilmu Sosial dan Humaniora, 2025)
This research aims to analyze the role of laundry attendants in supporting service quality in the Housekeeping Department of Gran Puri Hotel Manado. Laundry attendants are an essential part of hotel operations, responsible for providing linen, towels, and other room amenities in a clean, neat, and usable condition. This study applies a qualitative descriptive method with data collection techniques including direct observation, semi-structured interviews, documentation, and interviews with 5 hotel staff members who work in the housekeeping department and are directly connected with the laundry section. The results show that laundry attendants play a significant role in maintaining room service quality, especially in aspects of cleanliness, availability, and timeliness of linen supply. Most staff members stated that cooperation between laundry and housekeeping runs well, although minor delays in linen delivery occasionally occur. Overall, laundry attendants are considered to perform well and are capable of supporting housekeeping service standards as well as enhancing guest satisfaction at Gran Puri Hotel Manado